2021
DOI: 10.1097/01.jaa.0000758224.29328.f4
|View full text |Cite
|
Sign up to set email alerts
|

Reasons PAs leave their jobs

Abstract: Purpose: Employee turnover is an important indicator that carries a heavy financial cost for healthcare organizations. Although previous research has highlighted some factors associated with turnover, the reasons physician assistants (PAs) leave their jobs are not fully understood. This study aimed to determine the most common reasons behind PA turnover. Methods: In 2019, the American Academy of PAs (AAPA) distributed a survey to all PAs with an eligibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Tetzlaff and colleagues reported the association between collaborative physician relationship and burnout among PAs in oncology back in 2018 and replicated those results in 2021 2. Bernard and I published a study showing that the third most common reason PAs quit their jobs was toxic management and/or work environment 3. I also wrote an editorial highlighting multiple studies that showed the detrimental effects of toxic behavior on clinicians, institutions, and even patient safety 4…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Tetzlaff and colleagues reported the association between collaborative physician relationship and burnout among PAs in oncology back in 2018 and replicated those results in 2021 2. Bernard and I published a study showing that the third most common reason PAs quit their jobs was toxic management and/or work environment 3. I also wrote an editorial highlighting multiple studies that showed the detrimental effects of toxic behavior on clinicians, institutions, and even patient safety 4…”
mentioning
confidence: 95%
“…2 Bernard and I published a study showing that the third most common reason PAs quit their jobs was toxic management and/or work environment. 3 I also wrote an editorial highlighting multiple studies that showed the detrimental effects of toxic behavior on clinicians, institutions, and even patient safety. 4 The sum total of these studies-and many more-confi rms what nearly everyone on the planet discovers sooner or later: interpersonal relationships matter.…”
mentioning
confidence: 99%